IMPLEMENTASI TEORI POLA BINA PADA MAJELIS TAKLIM DENGAN PENDEKATAN ILMU MANAJEMEN - khadijah khadijah (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2020)
The phenomenon that can be seen today is that the Taklim Assembly (MT) does not yet have a systemic methodology framework. The activities carried out by MT movers are limited to what they are. However, MT has contributed to the spread of Islam, that is why it is necessary to continue to strive so that the role of MT is increasingly optimal in the propaganda movement in the middle of the digital era. The implementation of management in the MT can be believed to be able to contribute to the progress of Islam, as exemplified by the Prophet Muhammad who successfully cadreed his friends (sahabat) into reliable preachers. The name of the management was not yet present, but practically the management content had already been applied. Only in the 20th century (Henry Fayol) management science was born.The strength of management science lies in how to organize and manage the institution so that it is effective and efficient so that it is achieved according to plan and its success can be measured. Along with the development of MT, it is not enough to just use management science, this science becomes an instrument as an approach to bridge the Theory of Development Patterns ( Teori Pola Bina, PB) that are considered more in line with the needs of MT, a theory that the authors found when conducting research to write a dissertation at the level S3 education at the State Islamic University (UIN) Syarif Hidayayullah, Jakarta. PB theory is loaded with meaning, both deductively and inductively to become a scientific methodology building on the dimensions of ontology, epistemology and axiology with the structure of institutional development, cadre formation, teaching materials / materials, creative economic empowerment, friendship (net working) and evaluation. This study uses a qualitative methodology of a type of research whose findings are not obtained through statistical procedures or other forms of calculation. the main source of this research is the library research (library research) with reference to the management literature, preaching book 2 and Islamic scholarship.Keywords : Majelis Taklim, Management, Majelis Taklim Resources and Theory of Development Patterns